The addition of lymphadenectomy to secondary cytoreductive surgery in comparison with bulky node resection in patients with recurrent ovarian cancer. Issue 3 (15th October 2018) - Bogani, Giorgio; Leone Roberti Maggiore, Umberto; Chiappa, Valentina; Ditto, Antonino; Martinelli, Fabio; Sabatucci, Ilaria; Mosca, Lavinia; Lorusso, Domenica; Raspagliesi, Francesco
Abstract: Objective: To evaluate the role of full lymphadenectomy in patients with isolated nodal recurrence of ovarian cancer. Methods: In a retrospective study, the data of women undergoing secondary cytoreduction at the National Cancer Institute, Milan, Italy, between January 1, 2001, and December 31, 2015, were collected and patients with isolated nodal recurrence were identified. Factors predicting for disease‐free interval (DFI) and overall survival were estimated using Kaplan–Meier survival analysis and Cox regression analysis. Results: Of the 199 consecutive patients whose data were collected, isolated nodal recurrence (defined as the presence of lymphatic disease) was observed in 35 women. Among this study cohort, lymphadenectomy and bulky node removal were performed in 11 (31%) and 24 (69%) patients, respectively. Women who underwent lymphadenectomy experienced better DFI compared with those who had bulky node removal only (median 21 and 12 months, respectively; P =0.019), and lymphadenectomy, but not bulky node removal, significantly improved rates of DFI ( P =0.043). No factors were independently associated with overall survival; however, a trend toward an improved overall survival rate was observed in patients undergoing complete resection at the time of primary surgery ( P =0.055). Conclusion: Lymphadenectomy at the time of secondary cytoreduction improved DFI but did not have a significant effect on overall survival. Abstract : Full lymphadenectomy, compared with bulky node resection only, was associated with improved disease‐free survival among women with recurrent ovarian cancer.